The Role of Natural Conditions and Resources in the Agricultural Development of Khorazm Region - Amanov A. K; Bozorova N.O; Sharipova G.B (Genius Journals, 2022)
This article focuses on the issues of using natural conditions and natural resources of Khorezm region from the point of view of agricultural use. Research methods such as systematic geographic analysis and geographic comparison were used to reveal the dependence of agriculture, which is an important branch of the region's economy, on the formation and development of natural conditions and natural resources, as well as on the long historical period and social environment. In the article, the specific characteristics of the natural conditions of the region and the correspondingly formed agriculture, water shortage and land salinity in the era of global climate change, as well as their solutions, as well as the natural resources available in the region and their agriculture The importance of rational use in the economy, in particular, the creation of proper and effective methods of land and water resources, was highlighted in a unique way
Keywords: natural conditions; climate; natural resource; agriculture